3 - Repression of Press Freedom in Nigerian Democratic Dispensations - Akinwale, Akeem Ayofe (Africa Development, 2021)
The Nigerian socio-political environment influences press freedom with adverse implications for education, information, entertainment and surveillance. A theoretical recognition of the press as the “fourth estate” connotes the capacity of the press to monitor the tiers of government (the legislature, the executive and the judiciary). However, the state monitors the press in Nigeria in a manner that negates the principle of the fourth estate. This article examines the repression of press freedom in Nigerian democratic dispensations. Using questionnaires and in- depth interviews, data were drawn from 440 members of staff of selected print and electronic press organisations in Lagos and Oyo states of Nigeria. Results showed that although the press facilitated the development of democracy, challenges to press freedom were frequent. Respondents largely confirmed that the press kept the public informed, entertained and enlightened, and it set standards and established values for public conduct. The findings showed that the proposed Freedom of Information Bill (FIB) would empower the press and promote democracy in Nigeria if passed into law and implemented. Therefore, it was recommended that press organisations should pursue their professionalism and the ethics of journalism rather than succumb to socio-political forces influencing the quantity and quality of information made available to the public. Political leaders in Nigeria should accommodate public opinion and press reports on necessities for socio- economic development before making any public interest decision.